2021
DOI: 10.54589/aol.34/3/249
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral mucosal lesions in an adult population from eight communities in Santo Domingo, Dominican Republic

Abstract: The purpose of the study was to evaluate the prevalence of Oral Mucosal Lesions (OMLs) in an adult population from Santo Domingo, Dominican Republic. 751 subjects from eight communities from Santo Domingo accepted the invitation to participate in an oral screening from October 2016 to January 2017. 248 subjects were evaluated and clinically examined, age range 18-86 years. A validated instrument was designed to record demographic factors, age group, gender, anatomical location, presence or absence of OMLs, ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…The prevalent type of smoking practiced by our study participants were cigarette smoking (73.3%) while the water pipe users were less (9.5%) , in accordance with Collin et al, study conducted in eight communities of Dominican Republic [23], while.Bibars et al, and ALSwuailem et al, reported that the prevalent type of smoking was water pipe in their study samples (24,25), this may be due to the rising appeal of water pipe use among young individuals rather than cigarette.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalent type of smoking practiced by our study participants were cigarette smoking (73.3%) while the water pipe users were less (9.5%) , in accordance with Collin et al, study conducted in eight communities of Dominican Republic [23], while.Bibars et al, and ALSwuailem et al, reported that the prevalent type of smoking was water pipe in their study samples (24,25), this may be due to the rising appeal of water pipe use among young individuals rather than cigarette.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of OOPML reported in studies can be influenced by the country or geographic region in which the study is conducted, the socioeconomic level of patients, and the methodologies used, which may explain the large variation observed among publications (4.9%–64.5%). 14 , 15 , 16 , 17 , 18 Our study demonstrated that 10.2% of the total number of patients seen at the Otorhinolaryngology Service of INI-FIOCRUZ had OOPML, similar to the prevalence observed in population-based studies. 16 , 18 …”
Section: Discussionsupporting
confidence: 84%
“…Age group and skin color can vary depending on the study, as some studies on OOPML report a similar distribution, 13 , 16 , 21 , 32 while others report a female majority. 6 , 9 , 14 , 16 , 32 The male predominance in the present study may be related to the higher frequency of GID and Squamous Cell Carcinoma (SCC), diseases which are more common in men; 33 , 34 , 35 in contrast, benign lesions, mainly inflammatory fibrous hyperplasia, occur more frequently in women. 6 , 9 , 13 Most of our patients had low education levels similar to that observed by Souza et al (2017).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations